Perancangan Kursi Santai dengan Kayu Bekas - Dwi Agus Susilo; Gunawan Ohammad; Dewi Tri Rahmawati (SULUH: Jurnal Seni Desain Budaya, 2019)
The wood craft industry is very familiar with the community. Both the industrial community andthe general public.The industry that has survived and developed today is the wood craft industry, one of which is innovation in the field of product design by utilizing batik technology and its coloring. Efforts to utilize batik technology and coloring can improve the quality of produc.